Outcome of intramedullary nailing treatment for intertrochanteric femoral fractures - Martin F. Hoffmann; Justin D. Khoriaty; Debra L. Sietsema; Clifford B. Jones (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Introduction The OTA/AO type 31 A3 intertrochanteric fracture has a transverse or reverse oblique fracture at the lesser trochanteric level, which accentuates the varus compressive stress in the region of the fracture and the implant. Intramedullary fixation using different types of nails is commonly preferred. The purpose of this study is to evaluate intertrochanteric femoral fractures with intramedullary nail treatment in regard to surgical procedure, complications, and clinical outcomes. Methods From one level 1 trauma center, 216 consecutive adult intertrochanteric femoral fractures (OTA/AO type 31 A3) were retrospectively identified with intramedullary nail fixation from 2004 through 2013. Of these, 193 patients (58.5% female) met the inclusion criteria. The average age was 70 years (range 19–96 years). Results Cephalomedullary nails were utilized in 176 and reconstruction nails in 17 patients. After the index procedure, 86% healed uneventfully. Nonunion development was observed in 6% and 5% had an unscheduled reoperation due to implant or fixation failure. Active smoking was reported in 16.6%. Current smokers had an increased nonunion risk compared to those who do not currently smoke (15.6% vs. 4.3%; p = 0.016). The femoral neck angle averaged 128.0° ± 5°. Fixation failure occurred in 11.1% of patients with a neck-shaft-angle < 125° compared to 2.6% (4/155) of patients with a neck-shaft angle ≥125° (p = 0.021). Patients treated with a reconstruction nail required a second surgical intervention in 23.5%, which was no different compared to 25.0% in the cephalomedullary group (p = 0.893). In the cephalomedullary group, 4.5% developed a nonunion compared to 23.5% in the reconstruction group (p = 0.002). Painful hardware led to hardware removal in 8.8%. All of them were treated with a cephalomedullary device (p = 0.180). During the last office visit, two-thirds of the patients reported no or only mild pain but most patients had reduced hip range of motion. Conclusion Intramedullary nailing is a reliable surgical technique when performed with adequate reduction. Varus reduction with a neck-shaft angle < 125° resulted in an increase in fixation failures. Patient and implant factors affected nonunion formation. Smoking increased nonunion formation. Utilization of a cephalomedullary device reduced the nonunion rate, but had higher rates of painful prominent hardware compared to reconstruction nailing.